Alfred Hitchcock presents: Multilingualism as a vehicle for… suspense. The Italian dubbing of Hitchcock’s multilingual films. - De Bonis, Giuseppe (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
This study aims to shed light on the role multilingualism plays in Alfred Hitchcock’s films, by examining the different solutions adopted by Italian audiovisual translators to cope with the multilingual situations represented. The comparative analysis carried out between the original versions of the thirteen multilingual films directed by Hitchcock and their Italian dubbed versions has identified three different macro-strategies: first of all, the neutralisation of the different languages present in the original version via dubbing the entire film into Italian. Secondly, the preservation of the different lingua-cultural identities through a combination of dubbing with other screen translation modalities such as contextual translation, and interpretation performed by one the film’s characters. Finally, a third strategy is the quantitative reduction of the multilingual situations present in the original version of the film, with all the inevitable consequences that this may have on viewers’ suspension of linguistic disbelief.